A Comparative Evaluation of Rotator Cuff Injuries of the Shoulder Joint using High Resolution Ultrasound and Magnetic Resonance Imaging - Shrestha, MS; Alam, A (Medical Journal of Shree Birendra Hospital, 2012)
Introduction: Pathology of the rotator cuff is the cause of most common problems at the shoulder joint and accurate diagnosis is essential for appropriate management. High-resolution real-time ultrasonography and MRI are successful imaging modalities for both rotator cuff and non–rotator cuff disorders and have important implications in the management of rotator cuff pathologies. This study was conducted to Compare the results obtained after the evaluation of rotator cuff injuries of shoulder joint by high resolution Ultrasonography and Magnetic Resonance Imaging. Methods: 50 patients with suspected rotator cuff injuries of the shoulder joint were included in this study over a period of 2years. Patients had presented with various complaints like prolonged pain in the shoulder joint with stiffness, restriction and difficulty in movement of the shoulder joint, traumatic injuries and recurrent dislocations of the shoulder joints. Results: Mean age was 41.6years ( range 15-80 ).Maximum patients were between 41-50 years (24%). 29 were males and 21 were females. In our study diagnostic accuracy of ultrasound in rotator cuff tears was 57. 14% for full thickness tears and 58.33 for partial thickness tears. The diagnostic accuracy of ultrasound in detection of complete tear of the supraspinatus muscle was 57.14% while that of MRI was 100%. Conclusion: High resolution Ultrasound being a dynamic study can be used as the first-line investigation for rotator cuff tear. Full-thickness rotator cuff tears can be identified using ultrasound and MRI with comparable accuracy. DOI: http://dx.doi.org/10.3126/mjsbh.v10i1.6443 Medical Journal of Shree Birendra Hospital Jan-June 2011 10(1) 9-14